Cardiovascular complications of modern multiple myeloma therapy: A pharmacovigilance study. Issue 2 (9th September 2022) - Al‐Yafeai, Zaki; Ghoweba, Mohamed; Ananthaneni, Anil; Abduljabar, Hamzah; Aziz, David
Abstract : Aims: Multiple myeloma accounts for over 10–15% of haematological malignancies. Continued molecular advances have resulted in the development of new drugs for treatment of multiple myeloma. Four drugs were approved by the Food and Drug Administration (FDA) in 2015, but their safety is not well defined. The aim of this study is to delineate the cardiovascular adverse events of these drugs. Methods: We reviewed the adverse cardiac events of newly approved FDA drugs since 2015 using the US FDA Adverse Events Reporting System (FAERS) database. We calculated the reporting odds ratio (ROR) with 95% confidence interval (CIs) for the drugs that have the highest incidence of cardiovascular adverse events. Results: Among the medications that have approved for multiple myeloma between 2015 and 2020, 4 novel drugs showed the highest incidence of cardiotoxicity. ROR (95% CI) for atrial fibrillation due to elotuzumab, ixazomib, daratumumab and panobinostat compared to other FAERS drugs was 5.8 (4.4–7.7), 1.9 (1.5–2.3), 4.8 (4.2–5.6) and 5.7 (4.1–8.1), respectively. The ROR (95% CI) for cardiac failure was 8.2 (6.4–10.5), 4.7 (4.1–5.4), 5.8 (4.9–6.7) and 5.6 (3.8–8.1) and ROR (95% CI) for coronary disease was 2.7 (1.9–3.9), 2.7 (2.3–3.2), 2.3 (1.9–2.8) and 4.6 (3.2–6.6) due to elotuzumab, ixazomib, daratumumab and panobinostat compared to all other drugs in FAERS. Conclusion: Our results demonstrated that certain newly approved antimyeloma therapies are significantly associated with previously unknown cardiotoxicity. These results warrant further studies and highlight the importance of considering the cardiac history of patients with multiple myeloma when utilizing these novel agents.